Reconstructing the Sighat ta’liq in the compilation of Islamic law: A preventive approach to gender-based violence - Asenda Hella Purwaninda; Emirza Nur Wicaksono` (Priviet Social Sciences Journal, 2026)
This study aims to analyze and formulate a model for reconstructing the sighat ta’liq (conditional divorce pronouncement) within the Compilation of Islamic Law (KHI). The goal is to transform it into a preventive instrument against gender-based violence in marriage while maintaining respect for Islamic legal values and the national legal system. The central issue addressed is the current weakness of the sighat ta’liq in its preventive function; its normative construction remains unilateral, reactive, and formalistic, leaving wives with inadequate protection. Using a normative legal method, this study employs a document analysis approach to examine the KHI, relevant marriage laws, and the latest national and international academic literature. The analysis focuses on gender equity, human rights, and maqāṣid al-syarī‘ah (the higher objectives of Sharia) to evaluate the normative relevance and conceptual reconstruction of sighat ta’liq. The findings indicate that while the sighat ta’liq possesses strong normative potential as a protective mechanism, its effectiveness depends on a reconstruction that emphasizes the wife’s participation, legal certainty, and preventive sanctions against gender-based violence. An ideal reconstruction model would reposition the sighat ta’liq as a gender-equitable marriage contract clause that harmonizes maqāṣid al-syarī‘ah with the national legal framework. In conclusion, reconstructing the sighat ta’liq can strengthen legal protections for wives, prevent gender-based violence, and contribute to the evolution of a gender-responsive Islamic family law theory. These findings have practical implications for policy reform within the KHI, strengthening religious court mechanisms, and future research on the implementation of justice-based Islamic law.